2018
DOI: 10.3390/nu10020181
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Status of Various Ethnic Groups Living in New Zealand: An Analysis of the Adult Nutrition Survey 2008/2009

Abstract: Vitamin B12 deficiency leads to serious health problems, whilst sub-optimal status is associated with raised biochemical markers of disease risk. Identifying at-risk groups could benefit both individuals and public health. Dietary data were sourced from the New Zealand Adult Nutrition Survey 2008/2009, involving a nationally representative sample of 4721 participants. Ethnic groupings were by regional origin: Māori and Pacific Islands, New Zealand European, East and South-East Asian, and South Asian. Diets wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…However, the Ministry includes South Asian within the group Asian. We show a difference in diet between Asian and South Asian reflecting known differences in dietary patterns [20], otherwise our findings for vegetable and fruit intake are similar to the national survey.…”
Section: Discussionsupporting
confidence: 53%
“…However, the Ministry includes South Asian within the group Asian. We show a difference in diet between Asian and South Asian reflecting known differences in dietary patterns [20], otherwise our findings for vegetable and fruit intake are similar to the national survey.…”
Section: Discussionsupporting
confidence: 53%
“…Another observational study by Carmel et al [ 23 ] reported that vitamin B12 deficiency was most common in elderly white men and least common in black and Asian American women. A large cross-sectional survey conducted in New Zealanders aged ≥ 15 years showed that Māori/Pacific and East/South-East Asian groups had the highest vitamin B12 levels, whereas those most at risk of low vitamin B12 status were South Asians, including people with ancestral origins in the Indian subcontinent[ 24 ]. Māori and Pacific Island groups were the least likely to have inadequate vitamin B12 intakes compared with New Zealand Europeans, while the latter group was more likely to have an adequate vitamin B12 status compared with South Asians[ 24 ].…”
Section: Causes Of Vitamin B12 Deficiencymentioning
confidence: 99%
“…Fe deficiency with anaemia was defined as serum ferritin <12 μg/l and Zn protoporphyrin >60 μmol/mol and low Hb (33) . The cut-off for vitamin B 12 deficiency was <148 pmol/l (200 g/ml) and depleted was 148-221 pmol/l (35) .…”
Section: Biochemical Indicesmentioning
confidence: 99%